DETERMINING THE MARKET LEADER OF RESIDENTIAL HOUSING AND PROPERTY USING ANALYTICAL HIERARCHY PROCESS (AHP) CASE STUDY : CITRALAND AND TAMANSARI METROPOLITAN IN MANADO - Wenur, Try Setiawan; Massie, James D.D; Tumbuan, Willem J.F.A (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract : In Manado, there’s Citraland and Tamansari Metropolitan. As the result of modernization and development in this city that increasing day by day, it’s helps people and the economic waves in this area. Home and property are readily available and come right to the people to live in modern area. People can choose which place they want to live in. This is particularly so in Manado because of the fast pace of economic development and the limited availability of land. Rapid economic growth has increased the demand for more and better residential, commercial, and other premises. Property development and especially redevelopment have to fulfill these fast-changing requirements. This research aims to know which criteria is most important for customer in selecting a property and housing development in Manado and the market leader of property and housing development for the customer. This research used analytical hierarchy process with the sample which 75 respondents that were obtained from citizen in Manado. The result from this research shown that price is the most important criteria for the consumer to choose a property and housing development. The consumer wants an affordable price for the property. Tamansari is the market leader of residential housing and property. Keywords : analytical hierarchy process, marketing, market leader, consumer purchase decision